Users' Needs Report on Play for Children with Disabilities. Parents' and children's views - Zappaterra, Tamara (De Gruyter, 2017)
The needs of children and parents about play when the child has a disability are explored by mean on surveys to disability associations and families were collected during 2016 in 30 countries by members of the EU COST LUDI network Play for children with disability.The users' needs concerning play for children with disabilities are also explored by mean of case studies at a country level, based on literature reviews of avialable reports and emprirical studies in Finland, Lithuania and Sweden.